THE MALAYSIAN JOB MARKET: EXPLORING SOCIAL NETWORKING SITES (SNSS) AS AN ALTERNATIVE COMMUNICATION METHOD BETWEEN EMPLOYERS AND JOB SEEKERS - Elijah Noor Azmi; Nik Adzrieman Abdul Rahman, (INTERNATIONAL JOURNAL OF MODERN TRENDS IN SOCIAL SCIENCES (IJMTSS), 2024)
Interpersonal communication refers to the exchange of information, ideas, and feelings between two or more individuals. It is propounded as an essential component of human life; however, rapid technological advances have been changing the nature of interpersonal communication. As a result, the use of technology-oriented mediums like social networking sites (SNSs) has gained a prominent role in communication, particularly in the recruitment process. This subsequently alters the way employers and job seekers communicate with one another, which sparks the interest of researchers to further investigate the phenomenon. As an effort to contribute to the discussion, this paper reports an empirical study that investigated the use of SNSs in the communication between employers and job seekers. The objective is to understand the conceptualization of SNSs between employers and job seekers, the communication activities that occurred, the antecedents of choosing job advertisements from the job seekers’ perspective, and the consequences of using SNS platforms. This was achieved by adopting the Users and Gratification Theory as the underlying principle of the investigation. Purposive sampling was used to select 19 informants from various states in Malaysia. In-depth interviews were conducted to elicit data from these informants and it was later evaluated and combined in a thematic data analysis using the NVivo 12 software. The findings showed that the concept of quality communication comprises six (6) categories, namely data quality, reliability, matching and bridging, job security, opportunities for advancement, and transparency.